Analisis Pengendalian Biaya Operasional Pada Pt Midi Utama Indonesia tbk - Sudirman Abdi; Maryam Maryam (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
Controlling analysis of operational expense at PT Midi Utama Indonesia Tbk. This research aimed to find out controlling of operational expense which is determinated by PT Midi Utama Indonesia Tbk and to find out the things that caused operational expense was not effective and effecient . This research used variance analysis method of operational expense namely an analysis which had a function to compare operational expense that was valued with a real operational expense , so that was able to find out variance of operational expense the big variance was happened to gether with factors the caused to happen avariance so that if the management was able to acquire a feed back in doing controlling with executing of operational expense value in the next year so that the variance is able to handle.